Kecemasan Pranikah Dan Penanganannya - Wulandari, Ratna (STKIP Andi Matappa, 2018)
The study aims at examining (1) the symptoms of anxiety of pre-marital experienced by the bride and groom in West Tanete Riattang of Bone district, (2) the effectiveness of relectation to solve anxiety of pre-marital experienced by the bride and groom West Tanete Riattang of Bone district. The study employs qualitative approach with a case study. Data is obtained by employing interview, observation, and documentation. The data collection is then analyzed with qualitative descriptive analysis. The result of the study reveal that (1) the symptoms in forms of physical pre-marital anxiety experienced by ATR are: sleeping disorder, headache, lack of spirit; while the psychological impact is get angry easly, is because ATR imagines about the wedding process. In addition, she also thinks about the condition after marriage, such as can she manage the money, how to take care of the childre, and does her husband let her hang out with friend. Similiar to ART, the symptoms of pre-marital anxiety are also experienced by VFI physically and psychologically. The symptoms of pre-marital anxiety physically are like strained on her neck and sleeping disorder; while the psychological symptoms are lack of confidence and difficulty to concentrate. These are due to VFI think about the process of wedding feast, financial condition after marriage; (2) the problem solving of pre-marital anxiety is through the technique of systematic relactation given maximal result where all those two cases are already change through their ability to control themselves, to dismissed anxiety when imagining the wedding proscess.